A neural control model for bimanual rhythmic movements - Klaiman, E.; Karniel, A. (2004 23rd IEEE Convention of Electrical and Electronics Engineers in Israel, 2004)
Rowing a boat, playing drums, and performing surgery require bimanual coordination. Although bimanual coordination in rhythmic movements has been widely researched, the learning processes of these movements have gone largely unnoticed. A well known fact is that bimanual polyrhythms are difficult to perform. A recent study (Mechsner, F. et al., Nature, vol.414, no.1, p.69-73, 2001) has shown that, presented with altered feedback, subjects are able to perform such otherwise difficult tasks. Following this study, we hypothesize that the brain contains internal representation of the transformation between the perception and execution levels. Our hypothesis predicts gradual improvement in performance and an after effect. We have conducted an experiment in which subjects tapped their index fingers while receiving altered visual feedback and observed the improvement of performance as well as after effects that are fingerprints of the internal representation. We present a neural model which portrays these key phenomena associated with the learning dynamics of bimanual coordination.